Caractérisation et étude de l’effet antioxydant de la gelée royale - LAGRA, Fatima Zohra; MERIOUL, Saliha (My University, 2025)
Oxidative stress results from an imbalance between the production of free radicals and the body's antioxidant defenses, leading to cellular damage. In this context, apitherapy, particularly royal jelly, is attracting increasing interest due to its richness in bioactive compounds, notably polyphenols, known for their antioxidant properties.The objective of our study is to characterize royal jelly and evaluate its antioxidant activity through a series of complementary analyses. Physicochemical analyses (pH, conductivity, acidity, Brix, moisture), phytochemical screening, quantitative assays (polyphenols, flavonoids, tannins, sugars), FT-IR analysis, and antioxidant activity evaluation by three methods (DPPH, ABTS, and FRAP) were conducted.The results of the physicochemical analyses allowed us to determine the characteristics of the sample, while the phytochemical screening revealed the presence of secondary metabolites. Quantitative assays confirmed a moderate content of polyphenols, flavonoids, and tannins, contributing to the antioxidant effect.Furthermore, FT-IR analysis highlighted characteristic functional groups such as phenolic hydroxyls (–OH), carbonyls (C=O), and amides (N–H), reinforcing the hypothesis of a richness in bioactive compounds. The antioxidant activity showed that royal jelly has moderate antioxidant capacity, directly related to its chemical composition.These results confirm the antioxidant potential of royal jelly and support its use in natural approaches to combat oxidative stress.
Keywords: royal jelly, oxidative stress, FT-IR spectrum analysis, antioxidant activity